PENGEMBANGAN VIDEO PROMOSI BUKU MENUJU DIGITALISASI PERPUSTAKAAN STKIP TAMAN SISWA BIMA - Muhammad Yunan; Ita Fitriati; Ahyar (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The research objective of developing this book promotional video was to increase students' interest in reading in an interesting way. The conclusion obtained from this research is a book promotional video towards digitizing the STKIP Taman Siswa Bima library which has been tested for its feasibility. This research uses the Research and Development (R & D) method with the Borg and Gall development model starting from needs analysis, planning, development, testing, evaluation, updating, improvement, correction, modification and ending with product dissemination. According to the final evaluation by media experts, a percentage of 95% shows that the book promotional video that has been made is declared valid. Meanwhile, the final results obtained by small group participants in the book promotional video obtained a percentage of 88.3% which was declared Very Decent. The final results obtained by large group participants in the book promotional video obtained a percentage of 86.5% which was declared Very Decent. According to the results of the study, the mean percentage (%) results involving 30 students obtained a percentage of 86.7% in the Very Eligible classification.